An Integrative Model for Transformative Learning - Charity Johansson (Adult Education Research Conference, 2008)
Transformative learning is a growing focus of study with input from many areas of adult education. This paper presents a model of transformative learning that integrates key scholarly contributions to transformative learning theory, providing a common framework and language for analyzing the transformative learning process.
Keywords: transformative learning; model; adult education